2009
DOI: 10.1038/nrendo.2009.177
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and molecular basis of idiopathic hypogonadotropic hypogonadism

Abstract: Idiopathic hypogonadotropic hypogonadism (IHH) has an incidence of 1–10 cases per 100,000 births. About 60% of patients with IHH present with associated anosmia, also known as Kallmann syndrome, characterized by total or partial loss of olfaction. Many of the gene mutations associated with Kallmann syndrome have been mapped to KAL1 or FGFR1. However, together, these mutations account for only about 15% of Kallmann syndrome cases. More recently, mutations in PROK2 and PROKR2 have been linked to the syndrome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
255
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(271 citation statements)
references
References 78 publications
3
255
0
7
Order By: Relevance
“…At birth, GnRH neurons have reached their final destination in the brain and many of them project into the median eminence, where they release the GnRH decapeptide from their axon terminals into the hypophyseal portal vasculature. 1 GnRH acts via the GnRH receptor, which is expressed on gonadotropic cells in the anterior pituitary gland. This action regulates both synthesis and release of gonadotropins such as luteinizing hormone (LH) and follicle-stimulating hormone (FSH), which control gonadal maturation and adult reproductive physiology via the hypothalamic-pituitary-gonadal (HPG) axis.…”
Section: Biology Of the Gnrh Neuronal Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…At birth, GnRH neurons have reached their final destination in the brain and many of them project into the median eminence, where they release the GnRH decapeptide from their axon terminals into the hypophyseal portal vasculature. 1 GnRH acts via the GnRH receptor, which is expressed on gonadotropic cells in the anterior pituitary gland. This action regulates both synthesis and release of gonadotropins such as luteinizing hormone (LH) and follicle-stimulating hormone (FSH), which control gonadal maturation and adult reproductive physiology via the hypothalamic-pituitary-gonadal (HPG) axis.…”
Section: Biology Of the Gnrh Neuronal Systemmentioning
confidence: 99%
“…Some key molecules have been discovered through the study of the genetics of CHH. 1 Inactivating mutations in genes encoding kisspeptin-1 (KISS1) 40 and its receptor (KISS1R) 41,42 halt pubertal development in humans. Extensive experimental studies in various species have demonstrated that kisspeptin-producing neurons are major afferents to GnRH neurons and are essential for different aspects of GnRH function, ranging from the tonic feedback control of GnRH and/or gonadotropin secretion to generation of the pre-ovulatory surge responsible for ovulation.…”
Section: Biology Of the Gnrh Neuronal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 A detailed description of the congenital forms of HH is already provided in this issue by Dr Rey and Dr Grinspon. The list of candidate genes (Table 2) both for normosmic HH and Kallmann syndrome is constantly growing and genetic testing should be based on the patient's gender, family history (if any), mode of disease inheritance, and the presence of additional clinical anomalies.…”
Section: Hypogonadotrophic Hypogonadismmentioning
confidence: 99%
“…In about 30-40% of patients mutation in one (or more than one) candidate gene(s) can be now identified. 4 The diagnosis of acquired HH, is of importance not only with respect to infertility but also for its potential implications to general health (in some cases it may represent a life-threatening condition). In fact, acquired HH can be related to tumours (both benign or malignant), and may affect the secretion of more than one pituitary hormone leading to their deficit or excess.…”
Section: Hypogonadotrophic Hypogonadismmentioning
confidence: 99%